Tujuan Eksistensi Tradisi Lomban Kabupaten Jepara di Era Modern: Awal Mula dan Prosesi Upacara Lomban Jepara, Tatacara Pembuatan Perahu Khusus Upacara Lomban, dan Nilai-Nilai Praktik Keberagamaan dalam Upacara Lomban - alfaris, muhrafi (IAIN Ambon, 2024)
The purpose of this paper is to reveal the origin and procession of larung saji on the beaches around Jepara. Research data were obtained through literature review, observation, and interviews and analyzed with a qualitative descriptive approach. The results of the research are (1) The existence of the first (only) larung saji on the coast of the Java Sea was carried out in the 18th century, and (2) Gathek (a small boat specialized in lomban) is made with special provisions. Suggestions for further research include exploring the meaning of fasting for 3 consecutive days in the process of making gathek, analyzing the composition of materials for making gathek, experimental tests related to the size of the gathek boat (90 cm x 4 m) to evaluate the effect of size on the performance or usefulness of gathek, and the symbolic meaning of “Joyo Samudro” attached to gathek.